The Legal Framework on Sustainable Tourism: A Comparative Analysis between Mauritius, Maldives and Seychelles - Ambareen, Beebeejaun; Hurree, Ishika (Journal of Tourism, Sustainability and Well-being, 2024)
The world is witnessing a rise in the number of international tourists travelling which is mainly caused by the fall in travelling costs and higher living standards. However, this has caused numerous negative impacts on the economy, the environment and the society. In the context of Mauritius, tourism has always been seen as among its key pillars that sustain its economy and helped it to flourish. Consequently, the purpose of this research is to assess the efficiency, robustness and accuracy of the legal framework on sustainable tourism in Mauritius in dealing with new emerging challenges. To achieve the research objective, the black letter research method was adopted to collect secondary data by analysing the related laws on tourism in the context of sustainability and a comparative analysis with some other countries’ rules on the researched topic was conducted. The countries selected for the comparison are the Maldives and Seychelles. It is observed that although there is a legal framework for tourism that is currently in place, there are still gaps in the laws that make it challenging for tourism businesses to operate sustainably. Among other issues relating to the environment and the economy, the socio-economic aspect has been neglected.